CEMENT STABILISATION OF A SOIL FROM BARITO UTARA FOR ROAD CONSTRUCTION - Yosua
CEMENT STABILISATION OF A SOIL FROM BARITO U\'ARA FOR ROAD CONSTRUCTION, Yosua, 2000, Program Magister Sistem dan Teknik Jalan Raya, Program Pascasarjana, Institut Teknologi Bandung. This thesis describes a laboratory investigation of cement stabilisation of a soil from Barito Utara for road construction. The soil sample was taken from Muara Teweh, Barito Utara regency, Central Kalimantan province. According to the USCS and AASHTO systems the soil is classified as GC and A-2-6. Minerals present in the soil are quartz and kaolinite. Investigation of the soil indicated a 4 days soaked CBR value of 12.37%, UCS of 1.013 kg/cm2, Plasticity Index of 16.89% and Los Angeles abrasion of 53.40%. Therefore the soil exhibited low soil support, high Plasticity Index and high weight loss during abrasion and is an unsuitable material that needs to be improved to meet the standard specification for road sub-base and base course. The investigation was done on four combinations of soil-cement mixture. The Atterberg limit test on low cement content mixture gave only a slight improvement and could not achieve the standard specification for road sub-base and base course. This indicated that cement could not be used as a modifier (cement-modified soil). The strength characteristics of soil-cement, UCS and CBR, exhibited a significant increase as the cement content is increased in the soil. The swelling of the soil is almost eliminated by cement addition. The weight loss of soil-cement due to 12 cycles of wetting-drying showed a decrease as cement content increased in the soil. Volume change during wetting-drying reduced as more cement was added to the soil. Combination 94:6 (soil:cement, % by weight) provides a suitable and economical road sub-base course; UCS after 7 days curing is 18.289 kg/cm2 (>6kg/cm2), CBR value after 3 days curing and 4 days soaking is 159.64% (>20%), swelling value is 0.005% (<2%), weight loss from wetting-drying is 3.21% (<7%) and volume change is 1.84% (<2%). Combination 91:9 provides a suitable and economical road base course; UCS after 7 days curing is 23.190 kg/cm2 (>22kg/cm2), CBR after 3 days curing and 4 days soaking is 167.54% (>80%),swelling is 0.000% (<2%), weight loss from wetting-drying is 2.08% (<7%) and volume change is 1.38% (<2)